The Kinesiopathology of Thoracolumbar Spine Injuries in Throwing and Overhead Young Athletes - Hemn Mohammadi; Saeed Ghaeeni; Ghazal Mohammadi (Islamic Azad University, Hamedan Branch, 2018)
Objective: High load and intensity exercises often begin in the early teenage years and therefore the risk of musculoskeletal and overuse injuries sush as spine injuries among young athletes increases in most sports fields, especially in young athletes at overhead and throwing sports. The purpose of this study was to review the kinesiopathology of thoracolumbar spine injuries in throwing and overhead young athletes. Methods: Articles on the topic in the past two decades were searched in sush databasesas in PubMed Medline and Science Direct and articles with keywords like “Pitchers Spine”, “Throwers Spine”, “Pitchers Injuries”, and “Overhead Throwers Injuries”. Finally 24 papers were selected from among 134 papers. Results: Most of elbow and shoulder overuse injuries in throwing occur at preparation phase and deceleration phase. Muscle injuries in throwing and overhead young athletes, often include core muscle strain which includes internal and external oblique, transverse abdominal and in relatively high rates rectus abdominis and the core muscle strain rein jury. The damage to the posterior elements of the spine occur due to the rotation, hyperextension, and flexion during repetitive activities such as swing the bat and hitting. The incidence of scoliosis in throwing and overhead young athletes with asymmetric load distribution on the trunk and shoulders is very common. The discs of these athletes are prone to injury due to axial loading, hyperextension / flexion and rotation during the preparation exercises and also due to biomechanics of throwing, swing and services. Conclusion: Throwing skills can affect the entire kinetic chain. Force production in each segment of the body increases the load on the adjacent segments and ultimately injuries occurred in the weaker segments and joints of the body. Accordingly, it is recommended in assessing thoracolumbar injuries and development treatment plans for throwing and overhead athletes, dynamic stability of pelvis, lower back and core be evaluated. Following thoracolumbar spine injuries, the athletes should be allowed to return to play after achieving the free pain range of motion, and stability of lumbopelvic-hip complex, and progress in the rehabilitation plane to special sport exercise phase.